2019
DOI: 10.1364/oe.380753
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Seebeck nanoantenna-based infrared harvesters

Abstract: In this letter, the authors develop an optimized Seebeck nanoantenna design suitable for IR harvesting applications. The design is optimized via the so-called particle-swarm-optimization algorithm (PSO), an evolutionary algorithm able to drive the morphology of a nano-object towards an optimum. Along with the so-called nanoloading technique, efforts are subsequently addressed to understand the physical mechanisms behind the wave energy to voltage conversion, from both numerical and theoretical perspectives. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Recently, a bimetal dipole nanoantenna made from titanium (Ti) and nickel (Ni) was studied for IR harvesting devices by maximizing the Joule heating. [21] However, owing to the difference in thermal conductivity of the metals, less heat can be maintained at the hot junction because the heat tends to flow toward the material with higher thermal conductivity. [21][22][23][24] As a solution to this issue, a single metal nanoantenna was used to avoid heat spread such that the high temperature at the hot junction could be maintained.…”
Section: Infrared Thermoelectric Nanoantenna With Maximum Output Volt...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a bimetal dipole nanoantenna made from titanium (Ti) and nickel (Ni) was studied for IR harvesting devices by maximizing the Joule heating. [21] However, owing to the difference in thermal conductivity of the metals, less heat can be maintained at the hot junction because the heat tends to flow toward the material with higher thermal conductivity. [21][22][23][24] As a solution to this issue, a single metal nanoantenna was used to avoid heat spread such that the high temperature at the hot junction could be maintained.…”
Section: Infrared Thermoelectric Nanoantenna With Maximum Output Volt...mentioning
confidence: 99%
“…[21] However, owing to the difference in thermal conductivity of the metals, less heat can be maintained at the hot junction because the heat tends to flow toward the material with higher thermal conductivity. [21][22][23][24] As a solution to this issue, a single metal nanoantenna was used to avoid heat spread such that the high temperature at the hot junction could be maintained. [25,26] Previous studies revealed that a palladium (Pd) dipole nanoantenna integrated with a single metal Pd nano-thermocouple achieved a ∆T of ≈25 mK with a V oc of 0.03 µV.…”
Section: Infrared Thermoelectric Nanoantenna With Maximum Output Volt...mentioning
confidence: 99%
See 1 more Smart Citation
“…The operating principle is the same as that of the Seebeck effect, wherein we excite the nanoantenna designs with various laser wavelengths (650 nm, 940 nm, and 1550 nm) that detect voltages produced by the properties of intersecting materials. Compared to the state of the art, to our knowledge, this is the first time that peak percentage voltage hike detection is attained when utilizing infrared energy [26][27][28][29].…”
Section: Introductionmentioning
confidence: 97%
“…Meanwhile, bowtie structure fabricated using nanolithography in experiment is more tunable and reproducible compared to other dipole-like antenna designs [32][33][34]. Although bowtie nanoantenna have been widely used in the nanophotonics field [35][36][37], there are still many unresolved issues. To our best knowledge, the spectroscopy properties of surface-enhanced photoluminescence of bowtie nanoantenna, especially the SEF effect, have not be systematically investigated in theory.…”
Section: Introductionmentioning
confidence: 99%